Investigation of barriers to county-level seasonal influenza vaccine uptake among Medicare beneficiaries in the United States – 2018–2019 seasonal influenza season - Bo-Hyun Cho; Alissa O'Halloran; Jamison Pike (Vaccine: X, 2023)
Introduction: As most public health decisions are made at the local level, public health interventions implemented at the local level may vary by their own unique circumstances, such as demographic composition or the availability of resources. Our objective is to estimate and characterize county-level flu vaccine uptakes among Medicare-covered adults aged ≥65 years. Methods: The flu vaccine uptake was estimated from Medicare Fee-for-Service claims for those who continuously enrolled during the 2018–2019 flu season. County-level characteristics were obtained from Centers for Disease Control and Prevention (CDC)’s Minority Health Social Vulnerability Index and Behavioral Risk Factor Surveillance System data as well as Health Resources and Services Administration’s Area Health Resources File. A generalized linear regression was used to assess the relationship between selected characteristics and uptake. Results: A total of 30,265,047 beneficiaries from 3,125 counties were identified, of which 53% received a flu vaccination during the 2018–2019 flu season. For 3,006 counties with more than 500 Medicare beneficiaries, the mean county-level uptake was estimated to be 47.7%. The mean uptakes in counties designated as a health professional shortage area (HPSA) (42.6% and 48.4%, respectively), were lower than the uptakes for the non-HPSA counties (53.8%). Metro counties (53.2%) showed higher uptakes than non-metro counties (44.2%). Regression analysis results showed that the percent of working adults aged 18–64 years and female were positively associated, while the percent of Black and Hispanic adults were negatively associated. Proportions of persons with limited proficiency of English, college education or above, single parent families, multi-unit housing, and living in group quarters were positively associated and significant. Conclusions: The results confirmed that county-level flu vaccine uptakes are low, reflect persistent racial disparities in vaccine uptake, and that Medicare populations in medically underserved communities with lower socioeconomic status need more attention in improving flu vaccine uptake.